Various Nodal Lines in P63/mmc-type TiTe Topological Metal and its (001) Surface State - Lin, Peng; Fang, Fang; Zhang, Li; Li, Yang; Wang, Kai (Frontiers in Chemistry, 2021)
Searching for existing topological materials is a hot topic in quantum and computational chemistry. This study uncovers P63/mmc type TiTe compound—an existing material—is a newly discovered topological metal that hosts the various type of nodal line states. Different nodal line states normally exhibit different properties; they may have their individual applications. We report that TiTe hosts I, II, and hybrid type nodal line (NL) states at its ground state without chemical doping and strain engineering effects. Specifically, two type I NLs, two hybrid-type NLs, and one Γ - centered type II NL can be found in the kz = 0 plane. Moreover, the spin-orbit coupling induced gaps for these NLs are very small and within acceptable limits. The surface states of the TiTe (001) plane were determined to provide strong evidence for the appearance of the three types of NLs in TiTe. We also provide a reference for the data of the dynamic and mechanical properties of TiTe. We expect that the proposed NL states in TiTe can be obtained in future experiments.